Metode Peer Teaching Berbasis Lesson Study dalam Meningkatan Kompetensi Interpersonal Mahasiswa (Lesson Study-Based Peer Teaching Methods in Improving Student Interpersonal Competence) - Jimat Susilo; Hesti Muliawati; Elin Rosmaya; Umi Rachmawati (Indonesian Language Education and Literature, 2023)
This study aims to describe the use of lesson study for the learning community in learning in the Indonesian Language Learning Evaluation course. The target of learning is sixth-semester regular students in the Indonesian Language and Literature Education Study Program, Gunung Jati Swadaya University, Cirebon. Data were collected through observation sheets which had been filled in by the observers. Several indicators are used as guidelines for assessing student interpersonal competence, namely (1) initiation of interactions and relationships (2) assertion, (3) self-disclosure, (4) emotional support, and (5) management of interpersonal conflicts. The results of the study show that interpersonal competence has increased. This can be seen from the recapitulation of successive percentages, cycle 1 of 60%, cycle 2 of 70%, and cycle 3 of 87.87%. The implication of this research is the importance of education related to students' interpersonal competence in preparing themselves as prospective teachers at school.Penelitian ini bertujuan mendeskripsikan pemanfaatan lesson study for learning community pada pembelajaran pada mata kuliah Evaluasi Pembelajaran Bahasa Indonesia. Sasaran pembelajaran yaitu mahasiswa regular semester enam di Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Swadaya Gunung Jati Cirebon. Data dikumpulkan melalui lembar observasi yang telah diisi oleh para observer. Beberapa indikator yang dijadikan sebagai pedoman penilaian terhadap kompetensi interpersonal mahasiswa, yaitu (1) initiation of interactions and relationships (2) assertion, (3) selfdisclosure, (4) emotional support, dan (5) management of interpersonal conflicts. Hasil penelitian menunjukkan bahwa kompetensi interpersonal mengalami peningkatan. Hal ini dapat diketahui dari rekapitulasi persentase secara berturut-turut, siklus 1 sebesar 60 %, siklus 2 sebesar 70 %, dan siklus 3 sebesar 87,87 %. Implikasi dari penelitian ini yaitu pentingnya pendidikan terkait dengan kompetensi interpersonal mahasiswa dalam mempersiapkan diri sebagai calon guru di sekolah.